Parametric study on mutual coupling reduction for MIMO future 5G antennas / Hamizan Yon ... [et al.] - Yon, Hamizan; Abd Rahman, Nor Hana; Aris, Mohd Aziz; Jamaluddin, Mohd Haizal; Jumaat, Hadi (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper presents the development of a compact Multiple Input Multiple Output (MIMO) antenna using new structure integrated with C shaped parasitic element for mutual coupling reduction and antenna isolation improvement. The antenna has been designed to resonate at 16GHz for future 5G mobile band. The separation of the antennas has been set from 0.5 to 0.26 to investigate the mutual coupling between dual antenna elements. The novel C shaped parasitic element has been located around the main radiating patch with 1mm in width to reduce the mutual coupling between the dual element antennas. Meanwhile, the separation distance of 0.32 between the antennas has been chosen for the final antenna design due to its good performance. By using the novel C shaped parasitic element, the antenna isolation have reduced from -11.77dB for without parasitic condition to -23.92dB when parasitic element was included. The result shows 25.79% isolation improvement has been achieved for antenna with C shaped parasitic element. Furthermore, by introducing the parasitic element, the bandwidth have been improved 32.71% from the design without parasitic element. The antenna was simulated and optimized at 16 GHz using Computer Simulation Technology (CST) with permittivity, r = 2.2 and thickness, h = 1.57mm on Rogers RT-Duroid 5885 substrate. The antennas are matched at their corresponding frequency of operations. The simulation results have shown that the antenna works well.